PEMBUATAN ALAT PENDETEKSI KEBISINGAN UNTUK BUDIDAYA BURUNG LOVE BIRD BERBASIS ARDUINO DAN ANDROID MELALUI WIFI - Akhmad Baihari Salat (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2019)
Created a tool to increase Love Bird production so that farmers do not have to worry about the condition of the Love Bird bird if there is noise that will disrupt the bird while laying eggs.This research was conducted by making a detection device to provide information on the status of noise intensity through Android.Thus it can prevent the Love Bird from being stressed when incubating its eggs, the effect is that if the Love Bird sires are disturbed by sound, they will lay eggs outside their cages "glodok", or they will not incubate their eggs.Therefore the breeders must protect the Love Bird from sudden noise.This tool will detect outdoor noise in the enclosure, the sound sensor uses an analog sound sensor v2. This sensor will send data to the Arduino microcontroller. Then the Arduino microcontroller will process the data according to the program that has been made. Data that has been processed by the Arduino microcontroller will turn on the incandescent lamp, turn on the dc fan, send information to the android that there has been noise, and move the servo motor to close the window, so that noise does not enter the cage and disturb the laying birds. And also this tool can detect if the drum room is too hot then the dc fan lights up, and if the drum temperature is too cold it will turn on the incandescent lamp as a heater. In the application the user can see decibels at this time, and can see the history on what date and what time the noise has occurred. Kata Kunci: Arduino uno R3, noise, analog sound sensor v2, DHT11 sensor